Photoluminescence properties of Sm(III) complex with β-hydroxyketone ligand amplified by usage of biquinoline - Khatri, Savita; Manoj; Poonam; kumar, Rajesh; Khatkar, S.P. (Innovative Research Thoughts, 2017)
Here, Newer ternary Sm(III) ion complex, Sm(HDMPE)3.biq is synthesized through usage of solution precipitation method which is further characterized by numerous techniques such as elemental analysis, 1H-NMR, FT-IR and photoluminescence spectroscopy. Here, we have also probed luminescence decay time as well as color coordinates of the evolved complex. When the excitation of the evolved complex is monitored at 373 nm in solid state at room temperature, it showcased pure sharp emission bands from f-f transitions of samarium ion, 4G5/2→6H5/2, 4G5/2→6H7/2 and 4G5/2→6H9/2 at 564 nm, 600 nm and 646 nm respectively. The Sm(III) ion can be efficiently sensitized alone by 1-(2-hydroxy-4,6-dimethoxyphenyl)ethanone (HDMPE) but the introduction of ancillary ligand biquinoline (biq) have outcomed in amplified photoluminescence. The photoluminescence emission spectra showcased that ternary complex might be a promising candidate for usage in advanced displays and lighting systems.